(3TQM eMGSf GdeLGdSs - (3CHh ESMGb GHf OgGbs; (3GHf GdYQja , CHh GdYHGS CMeO Hf eMeO Hf ehSi Hf YWGA Gddg GdUfgGLj, GHf GdYQja,J (B536 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdOgGb bhd GdTjNGHf GdYQjabhdg GdeYQaI eMLjf s
(3BNQgG (B:s
(3abGd jG GHf GdNWGH CeG JQVi Cf jchf dge GdOfjG hdfG GdBNQI bdJ Hdi jG QShd Gddg Udi Gddg Ydjc , Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdQGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B164s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs